REPRESENTASI HOMOSEKSUALITAS DALAM FILM INDONESIA KONTEMPORER - Maimunah, Maimunah (ATAVISME, 2007)
This paper examines the emergence of non-normative sexual orientations in contemporary Indonesian films. Unlike the representation of sexuality in New Order Indonesian films, which centred on the female reproductive role and presented the nation as constructed of heterosexual families rather than individual citizens, a number of 200()s Indonesian films can be seen as negotiations of new understandings of sexual diversity and individual subjectivity. These films represent a challenge to monolithic and essentialist constructions of sexuality in Indonesia, and portray characters and situations in ways that seem to fulfil the five selection criteria which Griffin and Benshoff (2006) apply to the definition of 'queer' cinema. As such, they are indicative of a paradigm shift in Indonesian cinema, which needs to be studied in association with broader patterns of social and political change. The paper describes three categories in the representation of sexual minorities in contemporary Indonesian films. The first category is represented by films such as Arisanl and , Gie, which portray characters and situations deal with male homosexual subjectivity or homoeroticism. The second category concerns films of this type that portray female characters, such as Detik Terakhirand TentangDia. In the third category are films which depict waria (male to female transgender characters) and transsexuals, represented by Panggil Aku Puspa and Realita Cinta dan Rock n Roll. The paper examines these films in the light of Boellstorff's (2005) study of gay and lesbi communities and subjectivities in Indonesia, as a way of situating them in a larger cultural picture. It suggests that the makers of these films are attempting to change the perception of their audiences about non-normative sexualities, and investigates the strategic devices used by the film makers to subvert censorship codes and social taboos in a country where homosexual behaviour is accommodated, but homosexual identities remain outside the range of socially and culturally-sanctioned subjectivities.